OFFSET
1,1
COMMENTS
It is easy to check that with x = 6n^2, y = 6n^3 - 1, and this z = 6n^3 + 1, it satisfies the Diophantine equation x^3 + y^3 = z^3 - 2. Thus these are near-misses for Fermat equation.
LINKS
Harvey P. Dale, Table of n, a(n) for n = 1..1000
Index entries for linear recurrences with constant coefficients, signature (4, -6, 4, -1).
FORMULA
a(n) = 6n^3+1.
a(1)=7, a(2)=49, a(3)=163, a(4)=385, a(n)=4*a(n-1)-6*a(n-2)+4*a(n-3)- a(n-4). [Harvey P. Dale, Dec 12 2011]
G.f.: (-x^3+9*x^2+21*x+7)/(x-1)^4. [Harvey P. Dale, Dec 12 2011]
EXAMPLE
For n=1, a(1)=7 and 7^3 - 2 (=341) = 5^3 + 6^3.
For n=2, a(2)=49 and 49^3 - 2 (=117647) = 24^3 + 47^3.
MAPLE
MATHEMATICA
6*Range[40]^3+1 (* or *) LinearRecurrence[{4, -6, 4, -1}, {7, 49, 163, 385}, 40] (* Harvey P. Dale, Dec 12 2011 *)
PROG
(PARI) a(n)=6*n^3+1 \\ Charles R Greathouse IV, Nov 29 2014
(Magma) [6*n^3+1 : n in [1..50]]; // Wesley Ivan Hurt, Jan 09 2017
CROSSREFS
KEYWORD
nonn,easy
AUTHOR
Carlos Alves, Aug 05 2009
STATUS
approved